KOMPOSISI DAN SEBARAN BURUNG DI HUTAN LINDUNG KPHP SORONG SELATAN DI PAPUA BARAT (Compositions And Distribution Of Bird In Protected Forests South Sorong In West Papua) - warsito hadi; L Khayati; Y Komendi (Journal Penelitian Kehutanan FALOAK, 2018)
AbstractKPHP South Sorong is one of the existing protected areas. The composition and distribution of bird species in a protected area can determine the quality and condition of existing forests. The approach of exploratory and population methods is used to determine the diversity of bird species present in the location. From 4 (four) location observations, at least obtained 34 species from 14 families in protected forest area KPHP south Sorong. The condition of degraded forests has an impact on the acquisition of bird species. Birds of the small vertebrate eater group (35%) dominate this area, compared to the fruiting birds (32%) and both insects, small vertebrates and fruits (30%). While high utilization by the community, the impact on the lack of large animals in protected areas KPHP Sorong south West Papua. Keywords: Composition, distribution, birds, protected areas, KPHP and West Papua